Glycaemic control and hypoglycaemia during 12 months of randomized treatment with insulin glargine 300 U/mL versus glargine 100 U/mL in people with type 1 diabetes (EDITION 4). Issue 1 (8th August 2017) - Home, Philip D.; Bergenstal, Richard M.; Bolli, Geremia B.; Ziemen, Monika; Rojeski, Maria; Espinasse, Melanie; Riddle, Matthew C.
Abstract : Aims: Insulin glargine 300 U/mL (Gla‐300) offers a flatter pharmacodynamic profile than insulin glargine 100 U/mL (Gla‐100). We have compared these insulins over 1 year in people with type 1 diabetes (T1DM). Methods: EDITION 4 was a 6‐month, multicentre, randomized, open‐label phase 3 study. People with T1DM who completed the 6 months continued randomized Gla‐300 or Gla‐100 once daily, morning or evening, for a further 6 months. Results: Among 549 participants randomized, 444 completed the 12‐month study period (Gla‐300, 80%; Gla‐100, 82%). Mean HbA1c decreased similarly from baseline to month 12 in the 2 treatment groups (difference, 0.02 [95% CI, −0.13 to 0.17]) %‐units [0.2 (−1.5 to 1.9) mmol/mol]), to a mean of 7.86 %‐units (62.4 mmol/mol) in both groups. For morning vs evening injection, there was no difference in HbA1c change over 12 months for Gla‐100, but a significantly larger decrease in HbA1c was observed in the Gla‐300 morning group than in the Gla‐300 evening group (difference, −0.25 [−0.47 to −0.04] %‐units [−2.7 (−5.2 to −0.4) mmol/mol]). Mean glucose from the 8‐point SMPG profiles decreased from baseline, and was similar between the 2 treatment groups. Basal insulin dose was 20% higher with Gla‐300 than with Gla‐100, while hypoglycaemia event rates, analysed at night, over 24 hours, or according to different glycaemic thresholds, did not differ between treatment groups, regardless of injection time. Adverse event profiles did not differ between groups. Conclusions: In T1DM, Gla‐300 provides glucose control comparable to that of Gla‐100, and can be given at any time of day.